The Effect of Equal Channel Angular Pressing on Structure and Machining Quality of AA5052 - Filippov A. V. Andrey Vladimirovich; Tarasov S. Yu. Sergei Yulievich; Shamarin N. N. Nikolay Nikolaevich; Podgornykh O. A. Oleg Anatolievich; Filippova E. O. Ekaterina Olegovna (2018, 2018)
Title screen